Implementasi Proyek Penguatan Profil Pelajar Pancasila (P5) dalam Menanamkan Nilai Karakter Anak Usia Dini - Miftahul Ilmaa; Herman Syafri; Purwati Purwati (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This study examines the implementation of the Strengthening the Pancasila Student Profile (P5) Project at Tunas Muda 1 Kindergarten to instill character values in early childhood. This study takes a qualitative approach, employing a case study method. Data were collected through observation, interviews, documentation, and literature studies. The results show that performing arts activities are effective in instilling Pancasila values such as diversity, cooperation, and independence. The involvement of teachers, parents, and the school community is crucial for the success of this program. The P5 program can enhance children's cognitive and social skills. Evaluations indicate that this project-based learning method has a significant positive impact on children's development. Additionally, recommendations include improving school facilities and infrastructure, continuous training for teachers, developing more specific modules, and increasing parental involvement in school activities. The program is also recommended to be expanded to more schools across various regions to strengthen character education at the national level.